PENGARUH KEMAMPUAN KERJA DAN PROMOSI JABATAN TERHADAP KINERJA KARYAWAN CV WICKER KANE INDUSTRI CIREBON - Sari Laelatul Qodriah; Ika Andriyani (Value : Jurnal Manajemen dan Akuntansi, 2015)
The purpose to get information about how much work ability and career promotion of employee performance CV. Wicker Kane Industry Cirebon. While the purpose of this research is to study and determines how much influence employment and promotion Traffic on employee performance CV. Wicker Kane Industry Cirebon, and to learn and know how much work and promotion Traffic secar together employee performance CV. Wicker kane industry Cirebon . The population in this study were employees of CV. Wicker kane industry Cirebon. Sempel number as many as 48 people surveyed respondents. Sampling technique in this study by using sampling, is all existing employees in the CV. Wicker kane Industry Cirebon. The method used was a survey method, a method that aims to collect data on a large number of variables through interviews and questionnaires. The type used is the primer date (field study) is by distributing questionnaires to employees and to the company interviews, secondary data the date obtained by reading and studying books, lecture notes, literature and scientific articles. This study uses analytical testing is accompanied and regresi test validity, reliability and classical assumption . From these results, it can be seen that persial work ability (X1) has an influence on the performance of employees is 2,539 and promosi position (X2) has an influence on the work performance of employees is 3,554. While simultaneously it is known that the ability to work and promotion have an influence on the performance of employees with influence value of 0,224 (R2) or of 22.4 %. This shows that the ability to work and promotion have an influence on employee performance CV. Wicker kane industry Cirebon. Key Words : work ability, career promotion and employee performance